2019
DOI: 10.1080/15384101.2019.1706903
|View full text |Cite
|
Sign up to set email alerts
|

The double dealing of cyclin D1

Abstract: Abbreviations: aa, amino acid ; AR, androgen receptor; ATM, ataxia telangectasia mutant;ATR, ATM and Rad3-related; CDK, cyclin-dependent kinase; ChREBP, carbohydrate response element binding protein; CIP, CDK-interacting protein; CHK1/2, checkpoint kinase 1/2; CKI, CDK inhibitor; DDR, DNA damage response; DMP1, cyclin D-binding myb-like protein; DSB, double-strand DNA break; DNA-PK, DNA-dependent protein kinase; ER, estrogen receptor; FASN, fatty acid synthase; GSK3β, glycogen synthase-3β; HAT, histone acetylt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
108
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(124 citation statements)
references
References 125 publications
(182 reference statements)
0
108
0
1
Order By: Relevance
“…Additionally, the same research group [ 144 ] has investigated NiMOS containing a combination of siRNA against cyclin D1 (CyD1) and TNF-α (NiMOS-siRNA-CyD1). CyD1 is a protein involved in cell proliferation [ 161 ] and is overexpressed in IBD [ 162 , 163 ]. Similar effects with regards to TNF-α, cytokines, chemokines, histopathology and clinical improvements were observed whether the formulation contained siRNA against only TNF-α or CyD1—or a combination thereof given as a 1.2-mg/kg oral dose.…”
Section: Preclinical Studies On Local Tnf-α Inhibitionmentioning
confidence: 99%
“…Additionally, the same research group [ 144 ] has investigated NiMOS containing a combination of siRNA against cyclin D1 (CyD1) and TNF-α (NiMOS-siRNA-CyD1). CyD1 is a protein involved in cell proliferation [ 161 ] and is overexpressed in IBD [ 162 , 163 ]. Similar effects with regards to TNF-α, cytokines, chemokines, histopathology and clinical improvements were observed whether the formulation contained siRNA against only TNF-α or CyD1—or a combination thereof given as a 1.2-mg/kg oral dose.…”
Section: Preclinical Studies On Local Tnf-α Inhibitionmentioning
confidence: 99%
“…CCND1 is an important regulator of the G0/G1 transition in the cell cycle, and is often abnormally expressed in cancer and is a biomarker for cancer phenotype and disease progression [38] . CCND1 is an established human oncogene that is commonly overexpressed in tumor tissues, especially in lung cancer, melanoma and oral squamous cell carcinoma [32] .…”
Section: Discussionmentioning
confidence: 99%
“…The transmission of restriction points is coordinated by two cyclin families, namely the cyclin D family and the cyclin E family. The activation sequence is that the D-type cyclin binds and activates cdk 4 and 6, and then cyclin E activates cdk2 [11,12]. Cyclin E targets the components of the DNA synthesis machinery, leading to the assembly of the complexes required for DNA replication [29].…”
Section: Discussionmentioning
confidence: 99%
“…In the advancement of the cell cycle, cyclin and CDK form a cyclin-CDK complex that affects cell proliferation. Researchers have indicated that the cyclin D-CDK 4 complex controls cells in the G0/G1 phase, while the cyclin E-CDK 2 complex controls cells from the G0/G1 phase to the S phase [12]. In the current research, the role of Tle6 on spermatogonia cell proliferation and the cell cycle was investigated using an immortalized mouse spermatogonia cell line, C18-4.…”
Section: Introductionmentioning
confidence: 95%